Relevance of abnormal uterine bleeding issue in young women and its comprehensive solution considering 2021 Russian Guidelines - Galina E. Chernukha (IP Berlin A.V., 2022)
Abnormal uterine bleeding is a common problem in gynecology. It is a general term to describe menstrual disorders, including frequency, regularity, duration, and bleeding volume in non-pregnant women. Up to 1/3 of women experience this condition during their lifetime. Heavy menstrual bleeding not related to structural abnormality can be a serious health problem for many young women. It has a profound adverse impact on many aspects of their lives and increases the risk of iron deficiency anemia. However, up to half of these women consider the volume of menstrual blood loss normal, and physicians do not ask the relevant questions during counseling. The Russian Clinical Guidelines "Abnormal Uterine Bleeding" provide physicians guide to the assessment, management, and choice of treatment for women with heavy menstrual bleeding.